The possible effects of the magnetic declination on the wave polarisation coeffcients at the cutoff point - Aydo?du, M.; Özcan, O. (My University, 2001)
The dispersion relation and the wave polarisation coefficients of the electromagnetic waves in the ionospheric plasma have been obtained by considering the magnetic declination. If the magnetic declination is taken into account, the polarisation coefficients have real and imaginary parts. It is pointed out that the peculiarity of the real parts of the wave polarisation coefficients become more obvious in the vicinity of the frequency ?(= ?pe + ?pi) in the ionospheric plasma, while has no effect on the imaginary parts. This result is different from as in the absence of the magnetic declination.
Keywords: Dispersions; Electromagnetic waves; Polarization; Dispersion relations; Imaginary parts; Ionospheric plasmas; Magnetic declination; Real and imaginary; Real part; Magnetoplasma